Arteriovenous uterine malformation: case report - Lara Sánchez, Raúl D.; Rafaelano Miranda, Alexander J.; Hernandez Flores, Sara E.; Alvarez, Tania P.; Bizuet Cabrera, Jose M.; Huerta, Angel Lemus (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The case of a 49-year-old patient is reported, with a particular history of obstetric risk, who presented with severe transvaginal hemorrhage, was performed doppler arteriography and ultrasound, finding data suggestive of arteriovenous uterine malformation, surgery was decided due to heavy menstrual bleeding with anemia, the pathology report shows characteristics of an arteriovenous uterine malformation.